Evaluating the impact of educational technology professional development upon adoption of Web 2.0 tools in teaching - Doherty, Iain (Australasian Journal of Educational Technology, 2011)
Our paper reports upon and critically analyses findings from a two-year research project into the provision of continuing professional development for making purposeful use of Web 2.0 tools in teaching. Based on our research, we make recommendations for delivering effective continuing professional development workshops whilst also acknowledging the limitations of this form of continuing professional development. The advantages of alternative forms of professional development are discussed and implications for practice are outlined.